A Study of Effectiveness of Assertive Training Module on Assertive behavior and Self-Esteem among Nursing Students: Exploring the Impact of Assertiveness Training on Nursing Students' Communication and Self-Esteem (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Numerous analyses of nurses' roles in interdisciplinary care have found that nurses areseldom asked for their input during health team meetings or in casual interactions between colleagues.Furthermore, the level of assertiveness deficit needs to be clarified. Nurses require greater training inassertiveness, and the way through which they are educated and taught in this area needs moreexplanation. The following topics related to assertiveness in communication, handling conflicts, buildingone's self-esteem, and standing up for one's own rights are of particular interest to the researcher. Theseconcerns all play a part in how nursing is put into practice and assessed. Research on the factors thatinfluence assertive behaviour in nurses might lead to more effective training methods.